THE EFFECT OF PREDISPOSING, ENABLING AND REINFORCING ON EXCLUSIVE BREASTFEEDING - Zul Risma; Marniati Marniati; Teungku Nih Farisni; Fitriani Fitriani (RADJA PUBLIKA, 2022)
Exclusive breastfeeding is breastfeeding only for infants 0-6 months without providing other food or drinks other than breast milk. The low coverage of exclusive breastfeeding indicates that there is a problem with exclusive breastfeeding in the working area of the Meutulang Health Center. This study aims to determine the effect of Predisposing (Knowledge, Attitude, Action) Enabling (Maternal Nutritional Status) and Reinforcing (Culture) on exclusive breastfeeding in the working area of the Meutulang Health Center. The research method is quantitative with a cross sectional study design. The population in this study were mothers who had babies of 6-12 months totaling 44. The sample of this study used the total sampling method. The data analysis technique used univariate and bivariate analysis with simple linear regression test. The results showed that partially there was an effect of knowledge variable (0.001 < 0.05), action variable (0.017 < 0.05), and cultural variable (0.000 < 0.05) on exclusive breastfeeding. However, the attitude variable (0.986>0.05) and the mother's nutritional status variable (0.934>0.05) had no effect on exclusive breastfeeding. The conclusion of the study is that there is an influence of knowledge, action, culture on exclusive breastfeeding and there is no influence of attitude, mother's nutritional status on exclusive breastfeeding. It is hoped that the puskesmas and related institutions will more often hold outreach and socialization to the community, especially mothers about the importance of exclusive breastfeeding for 6 months.